Dietary phenolics and exercise complementation to delay aging at its source: a comprehensive review highlighting mitochondrial function - Zhang, Jiong; Zhu, Wen-Wen; Huang, Yong-Yao; Tang, Chuan-He (Frontiers in Aging, 2025)
BackgroundCurrently, aging issues are becoming more prominent, and the aging population is expanding. The reliance on medical or pharmaceutical means of combating aging and disease raises concerns about the long-term safety and economic impact. Therefore, sustainable and friendly strategies need to be explored urgently. Phenolic-rich antioxidant dietary regimens and exercise integrated into daily habits contain great anti-aging potential. Research on natural laws for anti-aging based on phenolics and exercise is in full swing.Scope and approachThe review first outlines the current status of aging and elucidates the root causes of aging. Second, the anti-aging mechanisms at the source through daily behaviors such as phenolic diets and exercise are introduced. Then, the combined anti-aging strategy of dietary phenolic supplements and exercise is proposed, providing a feasible basis for resource synergy between the two. Finally, constructive comments are made to guide practical implementation and future development.Key findings and conclusionsMitochondrial dysfunction and its ROS accumulation are the essence of aging pathogenicity, and its causes include lifestyle habits, age, and genes. The precise action on mitochondria through phenolics and exercise to ameliorate oxidative stress and maintain anti-aging function is in line with contemporary concepts of anti-aging. Although research on the combined effects of phenolics and exercise for anti-aging is scarce and faces multiple challenges, this new strategy is likely to be adopted as these issues are gradually resolved.